2017
DOI: 10.1002/rmb2.12037
|View full text |Cite
|
Sign up to set email alerts
|

Fertility preservation of patients with testicular cancer

Abstract: BackgroundTesticular cancer (TC) is one of the most common malignancies in young men of reproductive age. Although TC is a curable malignancy with a high survival rate, its treatment requires various cytotoxic modalities and negatively impacts spermatogenesis; therefore, the fertility preservation of patients with TC has been studied.MethodsIn order to give an overview of fertility preservation in patients with TC, the literature was reviewed. Original and review articles were identified and examined on the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 113 publications
0
15
0
Order By: Relevance
“…The etiology for impaired semen quality among sperm bankers with malignancy is unknown. Hypothesized mechanisms include autoimmune, endocrine, and stress-induced effects of cancer, as well as testicular dysgenesis among men with testicular cancer (Williams et al, 2009;Katz et al, 2013;Hamano et al, 2017). While it is beyond the scope of this study to propose mechanisms for the observed differences in semen quality, it is feasible that some or all of these factors may be involved.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The etiology for impaired semen quality among sperm bankers with malignancy is unknown. Hypothesized mechanisms include autoimmune, endocrine, and stress-induced effects of cancer, as well as testicular dysgenesis among men with testicular cancer (Williams et al, 2009;Katz et al, 2013;Hamano et al, 2017). While it is beyond the scope of this study to propose mechanisms for the observed differences in semen quality, it is feasible that some or all of these factors may be involved.…”
Section: Discussionmentioning
confidence: 91%
“…Hypothesized mechanisms include autoimmune, endocrine, and stress-induced effects of cancer, as well as testicular dysgenesis among men with testicular cancer (Williams et al, 2009;Katz et al, 2013;Hamano et al, 2017). Hypothesized mechanisms include autoimmune, endocrine, and stress-induced effects of cancer, as well as testicular dysgenesis among men with testicular cancer (Williams et al, 2009;Katz et al, 2013;Hamano et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TC is one of the leading malignancies in males of reproductive age . Although patients with TC are at higher risk of unfavorable semen parameters than those with other malignancies, the success rates with ARTs in those with TC are reportedly comparable with those with other malignancies . However, it remains unclear which parameters have an impact on outcomes of subsequent ART in cancer patients.…”
Section: Introductionmentioning
confidence: 99%